Mechanical Properties of Soft Rocks Subjected to Water-Rock Reaction and Cyclic Pressure - Wei Huang; Rui Feng; Huanran Fu; Jingyu Chen; Zili Feng (Advances in Civil Engineering)
Studying the mechanical properties of soft rocks subjected to water and cyclic loading would contribute to a better understanding of the stability analysis of soft rock engineering under the conditions of storm and carrier dynamics. In this paper, two soft rocks from Southwest China (i.e., muddy siltstone and silty mudstone) were selected as test samples. Uniaxial compressive tests were applied to investigate the strength and deformation characteristics under water-rock reactions. Meanwhile, triaxial tests were carried out to analyse the fatigue damage and failure characteristics by applying cyclic axial loading under different confining pressures. The results indicated a reduction in the uniaxial compressive strength (UCS) under saturated conditions, which is correlated with the disintegration resistance of soft rocks. Moreover, the samples exhibited a softening phenomenon due to water absorption and rock expansion, decreasing the elastic modulus. The triaxial tests demonstrated that axial strain accumulated with the number of loading cycles due to fatigue and even failed when applying increased cyclic loading with certain cycles. The cohesion decreased during cyclic loading, but the friction angle was relatively independent of the number of cycles. In addition, reductions in the dynamic elastic modulus and shear modulus decreased with increasing loading time. This study indicated that water and cyclic loadings could cause significant degradation of the strength and stiffness of soft rocks, which need to be considered carefully during the engineering utilization of such materials.